(untitled) (Mustansiria Dental Journal, 2018)
Alveolar bone loss is the atrophy of maxillary and mandibular bone that underlines and support the teeth lead to reduction in bone height and volume. The sample of this study was collected from patients who attended Al-Mammon center for specialist dentists. The patients usually complaing from bleeding gum, discomfort on eating and relative mobility of teeth. In this study 60 male patients with age between 20-49 years were selected and divided into three groups to assess bone loss by the aid of digital panoramic radiographs in the upper and lower anterior teeth. The results revealed that bone loss is more in lower anterior teeth than in upper anterior teeth in most of the age groups.